2002
DOI: 10.2466/pr0.2002.91.2.423
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and False Recall in the Deese/Roediger and McDermott Procedure: A Methodological Note on Sex of Participant

Abstract: Research suggests that individuals may differ in their susceptibility to false memory in the Deese/Roediger and McDermott procedure. Prior studies of differences have focused on the effects of age, personality, personal past history of abuse, and neurological status on false memory susceptibility. This study examined whether sex might also differentially influence false memory. After listening to a series of word lists designed to elicit false recall of nonstudied associates, 50 male and 50 female college stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…This included the absence of main effects of gender and interactions involving gender. This pattern replicates deMayo and Diliberto (2003; see also Seamon et al, 2002), who also found no gender differences but does not replicate Lenton et al (2001), who found that indirect stereotype associations can produce false memories using the DRM paradigm. The present experiment did not (intentionally) invoke traditional (or non-traditional) male or female stereotypes and still no false memory effect was observed that was related to gender.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This included the absence of main effects of gender and interactions involving gender. This pattern replicates deMayo and Diliberto (2003; see also Seamon et al, 2002), who also found no gender differences but does not replicate Lenton et al (2001), who found that indirect stereotype associations can produce false memories using the DRM paradigm. The present experiment did not (intentionally) invoke traditional (or non-traditional) male or female stereotypes and still no false memory effect was observed that was related to gender.…”
Section: Discussionsupporting
confidence: 88%
“…We also ensured that our females subjects were screened for childhood sexual abuse, which has been shown to affect false memory production in females, and both groups were statistically equated on a number of demographic and psychological variables. We also increased our sample size by 41% over that reported in Seamon et al (2002). These authors found no gender effects using 50 men and 50 women and concluded that more subjects would be required to show even moderate false memory effects.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations